The load of practice variability must be regulated in relation with learner expertise - Garcia-Herrero, J. A.; Sabido, R.; Barbado, D.; Martinez, I.; Moreno, F. J. (International Journal of Sport Psychology, 2016)
Variability of practice is an approach to improve motor learning which proposes the practice of task variations under the same underlying movement structure with differing requirements. Few studies have examined the effect of variability in relation to the level of expertise. This study explored the utility of practice variability in learning overarm throwing among young participants with varied levels of expertise in team-handball. Two groups of novices (n=29) and two groups of teamhandball players (n=34) practiced overarm throws under constant and variable practice. To assess the performance in the two treatments, we measured throw velocity, accuracy, and consistence. The results showed that expert players improved their accuracy only under practice variability. A statistically insignificant trend was found for novices who improved their accuracy only under constant practice conditions. Variability of practice seems to benefit only expert participants, while novices showed greater improvements in their performance under constant practice.